2008
DOI: 10.1590/s0103-50532008000600007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Habenaria petalodes Lindl. (Orchidaceae)

Abstract: Uma nova substância, denominada habenariosídeo {[(2R)-2-[(2,3,4,6-tetra-O-acetil-b-Dglicopiranosil)oxi]-2-(2-metilpropil)-1,4-dioxo-1,4-butanodiil]bis(oximetileno-4,1-fenileno) bis-b-D-glicopiranosídeo}, foi isolada das frações polares do extrato etanólico de Habenaria petalodes Lindl. (Orchidaceae), juntamente com duas substâncias conhecidas e estruturalmente relacionadas, a loroglossina e a militarina. Os flavonóides: isoquercitrina, isorramnetina 3-O-b-D-glicopiranosídeo e isorramnetina 3,7-di-O-b-D-glicopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…The anomeric configuration was regarded as b from the J-value (7.3 Hz) of the glucosyl, H-1. The positions of the glucose moieties were deduced to be C-5′ and 5″ from the correlation between glucosyl H-1 and C-5′ and 5″ in the 2D NMR heteronuclear multiple bond correlation (HMBC) data.As all the spectroscopic data, including the optical rotation, agreed with the reported data, 1 was identified as militarine (Aasen et al 1975;Cota et al 2008) (Fig. 2).…”
Section: Isolation and Structural Determination Of The Active Compoundssupporting
confidence: 82%
See 1 more Smart Citation
“…The anomeric configuration was regarded as b from the J-value (7.3 Hz) of the glucosyl, H-1. The positions of the glucose moieties were deduced to be C-5′ and 5″ from the correlation between glucosyl H-1 and C-5′ and 5″ in the 2D NMR heteronuclear multiple bond correlation (HMBC) data.As all the spectroscopic data, including the optical rotation, agreed with the reported data, 1 was identified as militarine (Aasen et al 1975;Cota et al 2008) (Fig. 2).…”
Section: Isolation and Structural Determination Of The Active Compoundssupporting
confidence: 82%
“…As all the spectroscopic data, including the optical rotation, agreed with the reported data, 1 was identified as militarine (Aasen et al . 1975; Cota et al . 2008) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that this Tokoro et al (1990) and Kanisawa (1993;Kanisawa et al, 1994) isolated the most abundant glucosides from green pods and identified them as glucovanillin, p-hydroxybenzyl alcohol glucoside, bis[4-(β-D-glucopyranosyloxy)-benzyl]-2-isopropyltartrate (glucoside A) and bis[4-(β-D-glucopyranosyloxy)-benzyl]-2-(2-butyl)-tartrate (glucoside B). These glucosides A and B were reported for the first time in vanilla and have a structure very similar to the loroglossins found in other Orchidaceae plants (Cota et al, 2008;Huang et al, 2004). Various other minor glucosides were identified after enzymatic hydrolysis: glucosides of vanillic acid, vanillyl alcohol, p-vinyl-guaiacol, acetovanillon, caffeic acid, ferulic acid, methyl-3,4-dihydroxycinnamic acid, 2-methoxy-4-cresol, homovanillyl alcohol, 3,4-dihydroxybenzoic acid, ethyl-4-hydroxy-3-methoxyphenylacetate, p-cresol, p-vinylphenol, methylsalicylate, p-hydroxybenzylethyl ether, p-hydroxybenzaldehyde, p-hydroxy cinnamic acid, cinnamic alcohol, cinnamic acid, phenethyl alcohol, 3-phenylpropanol (Kanisawa et al, 1994).…”
Section: Phytochemistrysupporting
confidence: 60%
“…Characterization of the sugar moieties from the mixture of quercetin 3-β-galactopyranoside (1) and quercetin 3-β-glucopyranoside (2) was performed according Cota et al 2008b.…”
Section: Resultsmentioning
confidence: 99%